Sociodemographic Factors Related to Perceived Physical Activity on Chilean Adults after COVID-19 Pandemic - Rodrigo Gallardo-Rodríguez; Felipe Poblete-Valderrama; Viviana Rodas-Kürten; João Paulo Vilas-Boas (MDPI AG, 2024)
The current study aimed to examine the relationship between sociodemographic variables (i.e., sex, age, marital status, educational level, socioeconomic status, and working mode) and physical activity levels declared by Chilean adults. The sample comprised 483 Chilean adults, 159 men (32.9%) and 324 women (67.1%) aged from 18 to 69 years old (36.5 ± 12.0). The participants completed an ad hoc sociodemographic online survey between December 2022 and March 2023 that included questions about characteristics of participants such as sex, age, educational level, household income, marital status, and working mode. Vigorous, moderate, and walking activities were measured using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), a self-administered questionnaire. Men declared significantly higher vigorous and moderated physical activity than women. People aged 18 to 25, single or unmarried, and with the lowest household income, showed significantly higher scores in vigorous physical activity than those aged 26 to 45, cohabiting with a partner or married, and middle household income, respectively. Regarding working mode, people working at their job site said walking more than people not working, working in a hybrid mode, and working online. Our findings suggest that promoting strategies that increase physical activity during the pandemic is necessary to avoid health problems.